STRATEGIES IN THE FIELD OF ENERGY CONSUMPTION AND ENERGY EFFICIENCY IMPROVEMENT OF THE REPUBLIC OF UZBEKISTAN - Khamdamova Gavhar Absamatovna (American Journals, 2024)
This article analyzes the aspects of systematization and implementation of strategies in the energy sector and improvement of energy efficiency in the republic. Effective energy security is achieved through the implementation of a deliberate strategy in this area, which covers government actions aimed at supporting national economic stability and security in the energy sector. The article also presents statistical data that provide an opportunity for a neutral analysis of the current state of the industry.
Keywords: Energy, energy efficiency, strategy, energy security, energy policy, modernization, concept.